Problematika Pembimbing dalam Membina Penyandang Tuna Grahita di Panti Sosial Bina Grahita Harapan Ibu Padang - Ariani, Fitria; Putri, Nur Syahadani (Indonesian Journal of Counseling and Development, 2024)
Mentally retarded children in social institutions often lack optimal care due to limited resources and support for supervisors. This study explores the challenges faced by dormitory supervisors caring for mentally retarded children at the Bina Grahita Harapan Ibu Padang Social Home, aiming to identify solutions for improved service quality, child independence, and well-being. A qualitative approach employing observation and interviews with seven supervisors was used. Supervisors reported challenges including diverse child needs, limited resources, inadequate training and support, emotional strain, and minimal social support. These findings highlight the need for comprehensive support programs, including training, to enhance supervisor capacity and improve child outcomes